The Influence of Demonstration Methods to Improve Student Learning Outcomes in Social Science Subjects - Nur Millawati; Siti Nurjanah; Andi Sriwijaya (Journal of English Language and Education, 2026)
Low learning outcomes in Natural and Social Sciences (IPAS) at the elementary school level are often caused by a lack of variety in learning methods and a lack of visualization of abstract concepts. Therefore, this study aims to examine the effect of implementing the demonstration method on improving sixth-grade student learning outcomes at SD Negeri 2 Karang Anyar. The approach used was quantitative, with a pre-experimental One-Group Pretest-Posttest design. The study sample involved 16 students selected using a total sampling technique. Data collection instruments consisted of a multiple-choice test and a teacher activity observation sheet. The analysis results showed an increase in the average score from 60.62 to 78.94. Furthermore, the Paired T-Test and Wilcoxon test yielded a significance value of 0.000 (0.05). Thus, the demonstration method has proven effective in improving student learning outcomes while facilitating a more concrete and meaningful understanding of concepts.